Novel integrated agricultural land management approach provides sustainable biomass feedstocks for bioplastics and supports the UK’s “net-zero” target - Ni,Y; Richter,GM; Mwabonje,ON; Qi,A; Patel,MK; Woods,J (Environmental Research Letters, 2020)
We investigate the potential in producing biodegradable bio-plastics to support the emergent 'Net-Zero' Greenhouse Gas (GHG) emissions targets in the UK. A 'cradle to grave' Life Cycle Assessment was developed to evaluate GHG mitigation potentials of bio-based polybutylene succinate plastics produced from wheat straw-only (single feedstock) or wheat straw plus Miscanthus (mixed feedstocks) agricultural supply systems. For scenarios using mixed feedstocks, significant carbon mitigation potentials were identified at catchment and national levels (emission reduction of 30 kg CO2eq /kg plastic compared to petroleum-based alternatives), making the system studied a significant net carbon sink at marginal GHG abatement costs of £-0.5 to 14.9 /t CO2eq. We show that an effective 'Net-Zero' transition of the UK's agricultural sector needs spatially explicit, diversified and integrated cropping strategies. Such integration of perennial bio-materials into food production systems can unlock cost-effective terrestrial carbon sequestration. Research & Development and scale-up will lower costs helping deliver a sustainable bioeconomy and transition to 'Net-Zero'.